Mengungkap Kekuatan Transformasi melalui Rasionalitas serta Kritisisme: Analisis Dialektika Pencerahan Max Horkheimer - Fitria, Fildza Nardina; Saumantri, Theguh (Media: Jurnal Filsafat dan Teologi, 2024)
The essay deals with the power of transformation through rationality and criticism (Max Horkheimer's Dialectical Analysis of the Enlightenment). It is a review article that discusses the main topic using a literature study. According to the Dialectics of Enlightenment, Horkheimer and Adorno's critical theory aims to bring about a critical consciousness. It leads to Aufklärung or Enlightenment. Horkheimer and Adorno critically observed that technological and scientific developments do not always create freedom. Instead, technology is often used as a tool of control and domination. Faced with these challenges, Horkheimer emphasized the importance of continuous criticism of social and cultural conditions. Criticism is considered a tool for exposing injustices and gaps that emerged amid the enlightenment. For Horkheimer, critical thinking is not just intellectual analysis, but rather a means of freeing humans from the shackles and alienation produced by false enlightenment. By understanding the dialectic of enlightenment, we can more wisely manage developments over time to achieve positive and sustainable transformation.